Prst kot učna snov v šolski geografiji - Petauer, Milena (Geografski obzornik, 2006)
The soil as a learning matter in school geography is evaluated as more demanding and less popular subject. Therefore it would be necessary to modernize the syllabuses both at the primary and secondary schools, where a better vertical and horizontal interaction of subject matters should be considered. A modernization of syllabuses would require the need of new student s books.
Keywords: geografija; geography; pouk; pedogeografija; prst (pedologija); tla; učni programi